The money minders : the parables, trade-offs and lags of central banking - Chadha, Jagjit (Cambridge : Cambridge University Press, 2022)
In the crises of the past fifteen years, central bankers have become big public players in a drama that affects all our lives, involving financial market crashes, public health threats and devastating economic downturns. Having played a lead role in the global financial crisis and the coronavirus crisis, they are now being asked to broaden their appeal. But the key aim has always been one of simply ensuring monetary and financial stability. In this book, NIESR director Jagjit Chadha unpacks the world of central banking, explaining in accessible language the analytical techniques, policy toolkits or simple story-telling that they use to understand the economy, to implement monetary policy and to communicate their decisions to key decision-makers and the wider public.
Of Gold and Paper Money -- The Great Depression and Its Legacy -- Fine Tuning Out of Control -- A Science of Monetary Polity -- Where the Great Experiment Went Wrong -- A New Art of Central Banking -- Epilogue 1: Why Forecast? -- Epilogue 2: Monetary Policy in Troubled Times -- A Final Word.
Title from publisher's bibliographic system (viewed on 18 Feb 2022).
Keywords: Banks and banking, Central; Economic policy; Monetary policy